Evanescent-field-modulated two-qubit entanglement in an emitters-plasmon coupled system. (2nd July 2018) - Zhang, Fan; Ren, Juanjuan; Duan, Xueke; Chen, Zhao; Gong, Qihuang; Gu, Ying
Abstract: Scalable integrated quantum information network calls for controllable entanglement modulation at subwavelength scale. To reduce laser disturbance among adjacent nanostructures, here we theoretically demonstrate two-qubit entanglement modulated by an evanescent field of a dielectric nanowire in an emitter-AgNP coupled system. This coupled system is considered as a nano-cavity system embedded in an evanescent vacuum. Through varying the amplitude of evanescent field, the concurrence of steady-state entanglement can be modified from 0 to 0.75. Because the interaction between emitters and the nanowire is much weaker than that inside the coupled system, the range of modulation for two-qubit entanglement is insensitive to their distance. The evanescent field controlled entangled state engineering provides the possibility to avoid optical crosstalk for on-chip steady-state entanglement.